(untitled) (International journal of artificial intelligence, 2024)
The problem of analysing psychological aspects of motor activity of young people with disabilities is very relevant today. The problem of disability is global and very important for any country in the world. This article presents scientific information about the basic principles and principles of health promotion among people with disabilities. In addition, important conclusions about the importance of physical education and sport in the health of these individuals are outlined.